Child Temperament and Total Diurnal Cortisol in Out-of-Home Center-Based Child Care and in At-Home Parental Care - Katja Tervahartiala; Saara Nolvi; Susanna Kortesluoma; Juho Pelto; Sirpa Hyttinen; Niina Junttila; Annarilla Ahtola; Hasse Karlsson; Linnea Karlsson (Wiley, 2022)
The association between child temperament characteristics and total diurnal saliva cortisol in 84 children (M = 2.3 years, SD = 0.6) attending out-of-home, center-based child care and 79 children (M = 2.0 years, SD = 0.5) attending at-home parental care was examined. Saliva samples were collected during two consecutive days, that is, Sunday and Monday, with four samples taken per day. While children higher in surgency had higher total diurnal cortisol production, we did not find evidence that temperament moderated the associations between child-care context and total diurnal cortisol. Negative affectivity and effortful control were not related to cortisol output. Our findings suggest that temperamental surgency may be associated with higher total cortisol production in early childhood across child-care settings.